Microwave ablation combined with curettage for low-grade chondrosarcomas in the extremities: a single-center study - Kai Zheng; Xiuchun Yu; Ming Xu; Haocheng Cui; Wenqiang Xing; Qian Chen (BMC Musculoskeletal Disorders)
Abstract Background The surgical treatment of low-grade chondrosarcoma in the extremities remains a topic of controversy. This study aims to evaluate the clinical efficacy of microwave ablation combined with curettage in treating low-grade chondrosarcoma of the limbs. Methods We analyzed data from 17 patients who underwent microwave ablation for low-grade chondrosarcoma of the extremities over the past decade. Results were assessed based on general condition, surgical complications, local disease control, and functional outcomes as measured by the Musculoskeletal Tumor Society (MSTS) 93 scoring system. Results Among the 17 cases of low-grade chondrosarcoma, the distribution included 8 in the humerus, 7 in the femur, and 2 in the fibula. The median maximum diameter of the tumors was 5.5 cm (range: 4.0–8.2 cm), with a median follow-up of 53 months (range: 19–128 months). No patients required blood transfusions or experienced perioperative complications. The median surgical duration was 130 min (range: 60–150 min), and the average hospital stay was 7.9 days (range: 6–11 days). No local tumor recurrence or distant metastasis was observed during follow-up. Most patients reported minimal postoperative impact on limb functionality, with a median MSTS score of 28 (range: 20–30). Two patients sustained fractures; one underwent secondary internal fixation surgery and healed, while the other, with an asymptomatic microfracture, was monitored conservatively. Conclusions Microwave ablation combined with curettage is a viable option for local control in the treatment of low-grade chondrosarcoma in the extremities.